2007
DOI: 10.1038/sj.onc.1210952
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional interactions between STAT3 and KAP1

Abstract: Signal transducers and activators of transcription (STATs) mediate cell proliferation, differentiation and survival in immune responses, hematopoiesis, neurogenesis and other biological processes. For example, STAT3 has been reported to be constitutively activated in numerous cancer cells. To clarify the molecular mechanisms underlying the STAT activation, we performed yeast two-hybrid screening and identified KAP1/TIF1b as a novel STATbinding partner. KAP1 is a universal corepressor protein for the Kruppel-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 22 publications
2
78
0
Order By: Relevance
“…In our previous work, we have shown that KAP1 negatively regulates IFN-induced transcription by a transient reporter assay using the IFN-stimulated responsive element (ISRE)-LUC [12]. We further confirmed that KAP1 affects IFN-induced transcriptional activation and gene expression using siRNA to reduce the endogenous expression of KAP1 in HeLa cells.…”
Section: Kap1 Regulates Ifn-induced Gene Expression and Transcriptionsupporting
confidence: 63%
See 2 more Smart Citations
“…In our previous work, we have shown that KAP1 negatively regulates IFN-induced transcription by a transient reporter assay using the IFN-stimulated responsive element (ISRE)-LUC [12]. We further confirmed that KAP1 affects IFN-induced transcriptional activation and gene expression using siRNA to reduce the endogenous expression of KAP1 in HeLa cells.…”
Section: Kap1 Regulates Ifn-induced Gene Expression and Transcriptionsupporting
confidence: 63%
“…Our previous study revealed that the C-terminal region of KAP1 (amino acids 394-835) interacts with ectopically expressed STAT1, STAT3, STAT4 or STAT6, but not with STAT2, STAT5a or STAT5b in 293T cells [12]. Here, we investigated whether wild-type STAT1 interacts with KAP1 and STAT1 phosphorylation state is involved in their interactions.…”
Section: Kap1 Physically Interacts With Stat1 In Vivomentioning
confidence: 91%
See 1 more Smart Citation
“…The immunoprecipitates from cell lysates were resolved on SDS-PAGE and transferred to an Immobilon filter (Millipore; Bedford, MA), which was then immunoblotted with antibodies. To measure STAT3 DNA binding, cell extracts were treated with the immobilized STAT3 consensus oligonucleotide-Sepharose conjugate (Santa Cruz) as described previously [22].…”
Section: Immunoprecipitation Immunoblotting and Dna Binding Assay Imentioning
confidence: 99%
“…Hep3B cells were treated with an siRNA-Lipofectamine 2000 (Invitrogen, Carlsbad, CA) mixture at 37 °C for 4 hrs, followed by addition of fresh medium containing 10% FCS as described previously [16].…”
Section: Methodsmentioning
confidence: 99%